2019
DOI: 10.1590/1414-431x20198549
|View full text |Cite
|
Sign up to set email alerts
|

Association between MCP-1 -2518A>G polymorphism and asthma susceptibility: a meta-analysis

Abstract: The published data on the association between MCP-1 -2518A>G polymorphism and asthma susceptibility are inconclusive. Therefore, we performed a meta-analysis to estimate the impact of MCP-1 -2518A>G polymorphism on asthma susceptibility. PubMed, Web of Science, Wanfang, and China National Knowledge Infrastructure (CNKI) databases were used to identify eligible studies. The pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were used to calculate the strength of association. Sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Being an African country, our contradicting results may be explained by a study done in 2014 which discussed gene -gene interactions among MCP genes polymorphisms in asthma, which suggested that there was no single polymorphism of MCP-1 or MCP-2 gene that was associated with asthma but rather a nonindependence of effect or a gene -gene interaction is often described as "epistasis" (20), that concept was not investigated in the current study which was conclusively investigating a single polymorphism regardless its interaction with possible other existing polymorphisms. Furthermore, we can consider asthma genetic heterogeneity with respect to regulation of MCP-1 expression to explain our result (21).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Being an African country, our contradicting results may be explained by a study done in 2014 which discussed gene -gene interactions among MCP genes polymorphisms in asthma, which suggested that there was no single polymorphism of MCP-1 or MCP-2 gene that was associated with asthma but rather a nonindependence of effect or a gene -gene interaction is often described as "epistasis" (20), that concept was not investigated in the current study which was conclusively investigating a single polymorphism regardless its interaction with possible other existing polymorphisms. Furthermore, we can consider asthma genetic heterogeneity with respect to regulation of MCP-1 expression to explain our result (21).…”
Section: Discussionmentioning
confidence: 62%
“…The analysis was stratified by ethnicity. Caucasian population showed an increased risk of asthma with MCP-1 -2518 A>G polymorphism, African population showed a protective effect and no significant association was found in the Asian population (20).…”
Section: Discussionmentioning
confidence: 79%
“…This suggested that not only the susceptibility to asthma, but also its severity could be determined by this gene in Cameroonians. However, some authors have rather found MCP-1 genes as a protective factor in Africans as opposed to Caucasians, however, few studies have been conducted to date to verify this assertion [ 20 ]. However, there is always a complexity of interaction between single-nucleotide polymorphisms (SNPs) that can vary within populations, hence the importance of increasing the number of studies in order to get a clearer picture [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 plays a key role in regulating monocyte chemotaxis and endothelial activation, as well as regulating the progression of inflammation and the production of proinflammatory cytokines. [ 23 ] Lee et al [ 24 ] have reported that the MCP-1 rs1024611 polymorphism is associated with Alzheimer disease, [ 24 ] asthma, [ 25 ] immunoglobulin A nephropathy, [ 26 ] lupus nephritis, [ 27 ] diabetic nephropathy, [ 28 ] and diabetic foot ulcer. Inhibition of MCP-1 or specific MCP-1 antagonist can inhibit the release of TNF-α, IL-1β, and IL-6 from macrophages.…”
Section: Discussionmentioning
confidence: 99%